2013
DOI: 10.1074/jbc.m113.468231
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Modes of Exocytotic Fusion Pore Expansion in Large Astrocytic Vesicles

Abstract: Background: Astrocytes release glutamate and D-serine by fusion of large vesicles. Results: Fusion occurs at a ring shape of the docked membrane, and the movement of fusion-produced membrane fragment expands the fusion pore. Conclusion: Two modes of fusion pore expansion are associated with full and partial collapses of large vesicles. Significance: Two fusion modes provide a novel mechanism for full and partial collapses of large vesicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…To confirm the effect of fendiline on endosomal vesicle formation and sorting, Panc1 cells were stained with FM1-43FX, a membrane probe for activity-dependent vesicle cycling [ 60 ]. Fluorescence microscopy of cells incubated with FM1-43FX and treated with fendiline for 6h showed a significant increase in the number and size of FM1-43 positive intracellular vesicles (Figure 7G and 7H ).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the effect of fendiline on endosomal vesicle formation and sorting, Panc1 cells were stained with FM1-43FX, a membrane probe for activity-dependent vesicle cycling [ 60 ]. Fluorescence microscopy of cells incubated with FM1-43FX and treated with fendiline for 6h showed a significant increase in the number and size of FM1-43 positive intracellular vesicles (Figure 7G and 7H ).…”
Section: Resultsmentioning
confidence: 99%
“…The current model of the platelet secretory process considers that a crucial step in exocytotic secretion is fusion of the membranes of secretory granules with the membranes of the open canalicular system (OCS)/plasma membrane (Lemons et al, 1997;Sudhof & Rothman, 2009;Fang & Lindau, 2014;Mellander et al, 2014). It is also recognized that in platelets, membrane fusion is mediated by the assembly of the SNARE (Soluble N-ethylmaleimide-sensitive factor Attachment protein REceptor) complex (Sudhof & Rothman, 2009;Peng et al, 2013). However, the central role of SNARE proteins in platelet secretion is still not certain (Golembiewska & Poole, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…From such studies in cultured astrocytes, the size of the vesicles is estimated to vary between ϳ30 -50 nm (43) and Ͼ300 nm (64,248). Even VGLUT-positive vesicles of several microns have been found in brain slice astrocytes, but these are produced by stimulating the astrocytes either mechanically or with high glutamate concentrations (184,326,445), suggesting that these vesicles are involved in release of gliotransmitters in pathological conditions. Moreover, localization studies have suggested that the three vesicular glutamate transporters, VGLUT1, VGLUT2, and VGLUT3, as well as the vesicular ATP transporter VNUT are all present in astrocytes.…”
Section: Vesicular Transportersmentioning
confidence: 99%